Analysis of Tourism Product Attributes on Visiting Decisions in Geopark Ciletuh Sukabumi - Jimmy Ruben Sihombing; Kurniawan Saefullah; Edwin Rizal (Green Publisher Indonesia, 2025)
The Geopark area in Ciletuh attracts attention with cliffs and various waterfalls that have various heights. A number of waterfalls such as Curug Cimarinjung, Curug Puncak Manik, Curug Sodong, Curug Cikanteh, Curug Ciatel, Curug Awang, and Curug Tengah can be seen from the beach in Ciletuh. In addition, the area has coral reefs that are home to many rare species of ornamental fish, as well as Mandra island, Manuk island, Kunti island, and white sandy beaches on Cikadal beach adjacent to Ciletuh bay. The purpose of this research is to find out how the strategy in implementing the use of Tourist Product Attributes to Geopark Ciletuh Sukabumi tourists, and how tourist product attributes influence tourist decisions to visit Geopark Ciletuh, and how the tourist experience while visiting Geopark Ciletuh can provide an increase in tourist product attributes. The research method used is a qualitative approach with a case study method. Data for this study were collected through observation and in-depth interviews with key informants. The interview results show that the application of tourism product attributes has had a significant positive impact. The geopark has successfully highlighted the natural beauty and geological diversity as the main attraction, building a reputation as an attractive destination for tourists. By providing a variety of adventure activities and educational tours, Geopark Ciletuh is able to cater to a wide range of visitor interests. Good infrastructure, such as well-maintained trails and informative signage, also enhance the visitor experience.